Can cooperatives/employee‐owned businesses improve 'bad' jobs? Evaluating job quality in three low‐paid sectors. (8th September 2021) - Jenkins, Sarah; Chivers, Wil
Abstract: Job quality has received increased attention from academics and policy makers across industrialized countries. Yet, there has been limited assessment of how job quality is impacted by different organizational forms, including cooperatives and employee‐owned businesses (EOBs). Although there has been growing interest in how cooperatives/EOBs impact on employee outcomes, comprehensive assessments of the range and reasons for varied employee outcomes in these settings are underdeveloped. To address these lacunae, this study examines whether cooperatives and EOBs can improve 'bad' jobs by examining three in‐depth qualitative case studies of different types of cooperatives/EOBs forms located in low‐paid sectors of the economy in Wales: social care, transport and manufacturing. In so doing, we seek to contribute to recent academic assessments of employee outcomes to explore whether job quality is influenced by different organizational forms, including cooperatives and EOBs. We extend existing discussions relating to salient explanations for job quality by developing a contextualized assessment to examine the extent to which workplace actors can improve 'bad' jobs.